HEAT AND MASS TRANSFER INVESTIGATION OF THIRD-GRADE WILLIAMSON-CASSON HYBRID NANOFLUID MODEL IN DARCY-FORCHHEIMER POROUS MEDIUM ACROSS EXPONENTIAL STRETCHING SURFACE INFLUENCED BY VISCOUS DISSIPATION - Rehman, Ali; İnç, Mustafa; Basha, D. Baba; Abas, Siti Sabariah Binti; Khan, Ilyas; Noor, N. F. M. (World Scientific Publ Co Pte Ltd, 2026)
The novel concept of hybrid nanofluids (HNFs) captivated scientists and researchers due to its remarkable thermal conductivities, which led to improved thermal performance. There are several applications for these fluids in the fields of technology and industry. A third-grade Williamson-Casson HNF model for magnetohydrodynamics over an exponentially stretched surface in a DF permeable medium is presented in this work. It covers the impacts of viscous dissipation (VD) as well as the analysis of heat and mass transfer (HMT). The established governing PDEs for momentum, energy, and concentration transfer are transformed into a collection of nonlinear ODEs using similarity transformations (ST). These transformed equations are solved using semi-numerical methods called HAM. It investigates how velocity field (VF), temperature field (TF), and concentration field (CF) are affected by changes in critical parameters such as thermal conductivity, third-grade fluid parameter, DF number, magnetic field (MF) strength, Williamson and Casson fluid parameters, and nanoparticle volume fractions (VLFs). The results show that the presence of an HNF increases thermal conductivity, which improves heat transfer efficiency. Additionally, VD and third-grade fluid characteristics significantly impact fluid flow and energy transfer. The recent research offers important new information for practical applications in thermal engineering systems, biofluid mechanics, and polymer processing.
Keywords: Expositional Stretching Surface; Third-grade Fluid; Williamson-Casson Model; Darcy-Forchheimer (DF) Porous Medium; HAM; Non-Newtonian (nN)